Employment with a Human Face: Balancing Efficiency, Equity, and Voice - Gomez, Rafael (Relations industrielles / Industrial Relations, 2004)
The book ,"Employment with a Human Face: Balancing Efficiency, Equity, and Voice," by John Budd, is reviewed.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Economic theory; International; Labor Unions; Labor relations; Labor standards; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z